Problematic screen media use in children and adolescents attending child and adolescent psychiatric services in a tertiary care center in North India - Venkatesh Raju; Akhilesh Sharma; Ruchita Shah; Ravikanth Tangella; Sana Devi Yumnam; Jyoti Singh; Jaivinder Yadav; Sandeep Grover (Indian Journal of Psychiatry)
Objective: The present clinic-based study aimed to evaluate screen media use among children and adolescents who had a mental disorder. Methods: Two hundred twelve parents of children and adolescents attending the child and adolescent psychiatric services were approached. They were asked to rate the screen media use of their child brought for psychiatric consultation using the Problematic Media Use Measure-Short Form (PMUM-SF). The DSM-5 criteria of internet gaming disorder (IGD) were applied using the PMUM-SF, which contained nine items equivalent to nine items of IGD. Results: The mean age of the patients was 13.16 years (SD: 4.06; range: 0.8–18). Only 28.3% (n = 60) were aged less than 12 years. The most common primary diagnosis was neurodevelopment disorder (n = 82; 38.7%), followed by neurotic disorder (n = 62; 29.2%) and mood disorder (n = 30; 14.2%). The most common screen media used was television (n = 121; 57.1%) followed by the mobile phone (n = 81; 38.2%). The average screen time was 3.14 hours, with a range of 0.5–7 hours, and more than two-third of children and adolescents used screen gadgets for more than the recommended duration. Slightly more than one-fourth (22.2%) of children and adolescents with mental disorders fulfilled the DSM-5 criteria of IGD. When those with and without screen media addiction were compared, those with screen media addiction were more often male, from joint or extended families, more often diagnosed with neurodevelopmental disorders and disruptive disorder, and were less often diagnosed with neurotic disorders. Conclusion: About one-fourth of the children and adolescents with mental disorders had screen media addiction, and two-thirds of them used screen media for more than the recommended duration.